Security Analysis of a „Location-stamping” Protocol for GPS Coordinates - Ádámkó, Éva (International Journal of Engineering and Management Sciences, 2017)
Due to the rapid growth of GNSS based techniques in everyday life a service which can provide certified location information given by GPS coordinates became a worth considering idea. We designed two protocols that can achieve this goal, these can provide authenticate location and time information for any device which has a GPS receiver. In this article, I would like to prove -with the help of ProVerif software tool-, the latter statement. I investigated the authenticity and data integrity properties of the protocol.